Critical Period of Competition between Peanut (Arachis hypogaea L.) and Weed - Muhammad Alghazali Adli; Edison Purba; Mbue Kata Bangun (Universitas Sumatera Utara, 2018)
The research was carried out at Tanjung Sari, Medan, where the weeds were predominated by Eleusine indica. The research was begun from November 2015 until February 2016. The weeding treatments consisted of 14 treatments (weed free from 0-2 weeks after planting (WAP); weed free from 0-4 WAP; weed free from 0-6 WAP; weed free from 0-8 WAP; weed free from 0-10 WAP; weed free from 0-12 WAP; without weeding from 0-2 WAP; without weeding from 0-4 WAP; without weeding from 0-6 WAP; without weeding from 0-8 WAP; without weeding from 0-10 WAP; without weeding from 0-12 WAP; weed free until harvest and without weeding until harvest). The treatments were arranged in randomized block design with three replicates. Parameter observed were plant height, number of branch, number of flowering, number of peas per plant, number of peas per plot, peas weight per plant, peas weight per plot, seed weight per plant, seed weight per plot, weight of 100 seed, kind of weed, dominant weed height and weed’s weight. The result showed that the weeding time for peanuts has no effect on the plant height and number of flowering, but sifnificantly affected the number of peas per plant, number of peas per plot, peas weight per plant, peas weight per plot, seed weight per plant, seed weight per plot and weight of 100 seed. The critical periode of competition between peanut and weed occurred at 14 to 35 day after planting.